Sequential Statistical Optimization of Media Components for the Production of Glucoamylase by Thermophilic Fungus Humicola grisea MTCC 352 - Ramesh, Vinayagam (Hindawi Publishing Corporation, 2014)
Glucoamylase is an industrially important enzyme which converts soluble starch into glucose. The media components for the production of glucoamylase from thermophilic fungus Humicola grisea MTCC 352 have been optimized. Eight media components, namely, soluble starch, yeast extract, KH(2)PO(4), K(2)HPO(4), NaCl, CaCl(2), MgSO(4) ·7H(2)O, and Vogel's trace elements solution, were first screened for their effect on the production of glucoamylase and only four components (soluble starch, yeast extract, K(2)HPO(4), and MgSO(4) ·7H(2)O) were identified as statistically significant using Plackett-Burman design. It was fitted into a first-order model (R (2) = 0.9859). Steepest ascent method was performed to identify the location of optimum. Central composite design was employed to determine the optimum values (soluble starch: 28.41 g/L, yeast extract: 9.61 g/L, K(2)HPO(4): 2.42 g/L, and MgSO(4) ·7H(2)O: 1.91 g/L). The experimental activity of 12.27 U/mL obtained was close to the predicted activity of 12.15. High R (2) value (0.9397), low PRESS value (9.47), and AARD values (2.07%) indicate the accuracy of the proposed model. The glucoamylase production was found to increase from 4.57 U/mL to 12.27 U/mL, a 2.68-fold enhancement, as compared to the unoptimized medium.